2011
DOI: 10.1177/0307174x1103800501
|View full text |Cite
|
Sign up to set email alerts
|

Aramid Pulp for the Reinforcement of Thermoplastic Elastomers

Abstract: Aramid pulp offers excellent potential for effective reinforcement of thermoplastic elastomers such as polyamides because of its highly fibrillated fibre structure and correspondingly large surface area. However, the disadvantage of aramid pulp is that it is not free-flowing and so cannot be metered effectively. For that reason continuous metering in processes such as compounding is virtually impossible. However, research and development work at TITK has resulted in a way of processing aramid (AR) pulp to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The authors successfully demonstrated a unique way of fabricating aramid fiber-reinforced PA prepregs for the IM technique. Fabricated composites showed decent tribological properties, which make them suitable for manufacturing components, such as gear wheels, deflection pulleys, etc., subjected to tribological loads [53]. Alumina nanoparticle-filled epoxy matrix and AF (Kevlar 49)-reinforced composite laminates were fabricated using RTM.…”
Section: Aramid Fiber and Its Hybrid Compositesmentioning
confidence: 99%
“…The authors successfully demonstrated a unique way of fabricating aramid fiber-reinforced PA prepregs for the IM technique. Fabricated composites showed decent tribological properties, which make them suitable for manufacturing components, such as gear wheels, deflection pulleys, etc., subjected to tribological loads [53]. Alumina nanoparticle-filled epoxy matrix and AF (Kevlar 49)-reinforced composite laminates were fabricated using RTM.…”
Section: Aramid Fiber and Its Hybrid Compositesmentioning
confidence: 99%
“…The fibrillation of aramid fiber can increase its surface area, so as to have a reinforcing effect in a low fiber content. 3 Although aramid pulp is in a different Aixin Zhong and Junrong Luo authors contributed to the work equally and should be regarded as co-first authors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Twaron1080 was selected as the raw material and through the refining process to make them fibrillated. Twaron1080 is a type of 6 mm chopped paraaramid fiber with a diameter of 12 μm and density of 1.44 g/cm 3 , and was obtained from Teijin, Netherlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation